Spirit wars : Native North American religions in the age of nation building - Niezen, Ronald (University of California Press, 2000)
Spirit Wars is an exploration of the ways in which the destruction of spiritual practices and beliefs of native peoples in North America has led to conditions of collective suffering--a process sometimes referred to as cultural genocide. Ronald Niezen approaches this topic through wide-ranging case studies involving different colonial powers and state governments: the seventeenth-century Spanish occupation of the Southwest, the colonization of the Northeast by the French and British, nineteenth-century westward expansion and nationalism in the swelling United States and Canada, and twentieth-c.